Longitudinal fMRI measures of cortical reactivation and hand use with and without training after sensory loss in primates - Hui-Xin Qi (NeuroImage, 2021)
In a series of previous studies, we demonstrated that damage to the dorsal column in the cervical spinal cord deactivates the contralateral somatosensory hand cortex and impairs hand use in a reach-to-grasp task in squirrel monkeys. Nevertheless, considerable cortical reactivation and behavioral recovery occurs over the following weeks to months after lesion. This timeframe may also be a window for targeted therapies to promote cortical reactivation and functional reorganization, aiding in the recovery process. Here we asked if and how task specific training of an impaired hand would improve behavioral recovery and cortical reorganization in predictable ways, and if recovery related cortical changes would be detectable using noninvasive functional magnetic resonance imaging (fMRI). We further asked if invasive neurophysiological mapping reflected fMRI results. A reach-to-grasp task was used to test impairment and recovery of hand use before and after dorsal column lesions (DC-lesion). The activation and organization of the affected primary somatosensory cortex (area 3b) was evaluated with two types of fMRI – either blood oxygenation level dependent (BOLD) or cerebral blood volume (CBV) with a contrast agent of monocrystalline iron oxide nanocolloid (MION) – before and after DC-lesion. At the end of the behavioral and fMRI studies, microelectrode recordings in the somatosensory areas 3a, 3b and 1 were used to characterize neuronal responses and verify the somatotopy of cortical reactivations. Our results indicate that even after nearly complete DC lesions, monkeys had both considerable post-lesion behavioral recovery, as well as cortical reactivation assessed with fMRI followed by extracellular recordings. Generalized linear regression analyses indicate that lesion extent is correlated with the behavioral outcome, as well as with the difference in the percent signal change from pre-lesion peak activation in fMRI. Monkeys showed behavioral recovery and nearly complete cortical reactivation by 9–12 weeks post-lesion (particularly when the DC-lesion was incomplete). Importantly, the specific training group revealed trends for earlier behavioral recovery and had higher magnitude of fMRI responses to digit stimulation by 5–8 weeks post-lesion. Specific kinematic measures of hand movements in the selected retrieval task predicted recovery time and related to lesion characteristics better than overall task performance success. For measures of cortical reactivation, we found that CBV scans provided stronger signals to vibrotactile digit stimulation as compared to BOLD scans, and thereby may be the preferred non-invasive way to study the cortical reactivation process after sensory deprivations from digits. When the reactivation of cortex for each of the digits was considered, the reactivation by digit 2 stimulation as measured with microelectrode maps and fMRI maps was best correlated with overall behavioral recovery.